México, Imperio y Estado. Consideraciones sobre tres conceptos significantes del virreinato - Rosenmüller, Christoph (El Colegio de México, A.C., 2025)
Many historians have argued that, when analyzing the viceregal period, it is anachronic or teleological to use “Mexico” to refer to the territory, “Mexican” for the people, “state” to refer to the governance of people and territories and “empire” as a term for a vast conglomerate of territories. Nevertheless, this article argues that these concepts increasingly appeared with these meanings in legal sources, official correspondence and the writings of the clergy, both in Latin as well as in Spanish, and so these expressions can be used by historians as analytical terms. Furthermore, “empire” and “state” underwent semantic changes in this period in response to the expansion of state power, while “Kingdom of Mexico” or “Mexican Viceroy” took on a broader territorial meaning than they had at the beginning of the colonial era.